Concealed spots and contemporary supranational ECEC policy - Pupala, Branislav (Universitas Negeri Semarang, 2017)
This article returns to the historical roots of ECEC and considers them within the context of contemporary international preschool education policy. Present-day policy is characterised by the high level of support directed at this education level. The reasons for this are largely economic and ECEC is becoming part of economic development strategy. Frequently research such as the HighScope Perry Preschool Program can be found in the background. In many ways contemporary ECEC is reminiscent of education policy under communism in Europe. This area represents a concealed spot in the international research on preschool education. The extensive expansion of nursery schools in these countries took place from the middle of the last century onwards. They were the first countries to create preschool curricula at the national level. They also often relied on the first attempt at an early years curriculum, contained in John Amos Comenius’s The School of Infancy (Informatorium of Maternal School).